Microvascular endothelial cells of the corpus luteum - Spanel-Borowski Katherina (Reproductive Biology and Endocrinology, 2003)
Abstract The cyclic nature of the capillary bed in the corpus luteum offers a unique experimental model to examine the life cycle of endothelial cells, involving discrete physiologically regulated steps of angiogenesis, blood vessel maturation and blood vessel regression. The granulosa cells and theca cells of the developing antral follicle and the steroidogenic cells of the corpus luteum produce and respond to angiogenic factors and vasoactive peptides. Following ovulation the neovascularization during the early stages of corpus luteum development has been compared to the rapid angiogenesis observed during tumor formation. On the other end of the spectrum, the microvascular endothelial cells are the first cells to undergo apoptosis at the onset of corpus luteum regression. Important insights on the morphology and function of luteal endothelial cells have been gained from a combination of in vitro and in vivo studies on endothelial cells. Endothelial cells communicate with cells comprising the functional unit of the corpus luteum, i.e., other vascular cells, steroidogenic cells, and immune cells. This review is designed to provide an overview of the types of endothelial cells present in the corpus luteum and their involvement in corpus luteum development and regression. Available evidence indicates that microvascular endothelial cells of the corpus luteum are not alike, and may differ during the process of angiogenesis and angioregression. The contributions of vasoactive peptides generated by the luteal endothelin-1 and the renin-angiotensin systems are discussed in context with the function of endothelial cells during corpus luteum formation and regression. The ability of two cytokines, tumor necrosis factor alpha and interferon gamma, are evaluated as paracrine mediators of endothelial cell function during angioregression. Finally, chemokines are discussed as a vital endothelial cell secretory products that contribute to the recruitment of eosinophils and macrophages. The review highlights areas for future investigation of ovarian microvascular endothelial cells. The potential clinical applications of research directed on corpus luteum endothelial cells are intriguing considering reproductive processes in which vascular dysfunctions may play a role such as ovarian failure, polycystic ovary syndrome (PCOS), and ovarian hyperstimulation syndrome (OHSS).